2019
DOI: 10.1002/wmh3.320
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Pathology: The Rhetoric of Pathology in Jane Doe's Struggle to Obtain an Abortion in Federal Immigration Custody

Abstract: In October 2017, the stories of Jane Doe, Roe, and Poe, young women detained at a Texas immigration detention center run by the Office of Refugee Resettlement (ORR) made national headlines. They were pregnant, undocumented immigrants who were denied access to abortion because the ORR argued that they were “not people for constitutional purposes.” Using rhetorical silence, paternalistic rhetoric, and dehumanizing rhetoric, ORR director Scott Lloyd had the ultimate power of definition that allowed him to rhetori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The 19 included articles were published between 2013 and 2022, with sample sizes ranging from 10 to 1,773 people (see Table 3 for article characteristics). Thirteen articles reported on qualitative findings (including two mixed-methods studies that only reported on qualitative data) (13/19 articles, 68.4%) [ 40 , 41 ], three quantitative (3/19 articles, 15.8%) [ 42 44 ], one mixed-methods (1/19 articles, 5.3%) [ 45 ], one scoping review (1/19 articles, 5.3%) [ 46 ], and one narrative review (1/19 articles, 5.3%) [ 47 ]. Of the 17 primary articles, four used convenience sampling (4/17 articles, 23.5%) [ 42 , 43 , 45 , 48 ], three used purposive (3/17 articles, 17.6%) [ 40 , 49 , 50 ], four used both purposive and snowball (4/17 articles, 23.5%) [ 51 54 ], two used purposive and convenience (2/17 articles, 11.8%) [ 41 , 55 ], one used informant-purposive and snowball (1/17 articles, 5.9%) [ 56 ], one used convenience and snowball (1/17 articles, 5.9%) [ 57 ], one used purposive, gatekeeper and snowball (1/17 articles, 5.9%) [ 58 ], and one used stratified random sampling (1/17 articles, 5.9%) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 19 included articles were published between 2013 and 2022, with sample sizes ranging from 10 to 1,773 people (see Table 3 for article characteristics). Thirteen articles reported on qualitative findings (including two mixed-methods studies that only reported on qualitative data) (13/19 articles, 68.4%) [ 40 , 41 ], three quantitative (3/19 articles, 15.8%) [ 42 44 ], one mixed-methods (1/19 articles, 5.3%) [ 45 ], one scoping review (1/19 articles, 5.3%) [ 46 ], and one narrative review (1/19 articles, 5.3%) [ 47 ]. Of the 17 primary articles, four used convenience sampling (4/17 articles, 23.5%) [ 42 , 43 , 45 , 48 ], three used purposive (3/17 articles, 17.6%) [ 40 , 49 , 50 ], four used both purposive and snowball (4/17 articles, 23.5%) [ 51 54 ], two used purposive and convenience (2/17 articles, 11.8%) [ 41 , 55 ], one used informant-purposive and snowball (1/17 articles, 5.9%) [ 56 ], one used convenience and snowball (1/17 articles, 5.9%) [ 57 ], one used purposive, gatekeeper and snowball (1/17 articles, 5.9%) [ 58 ], and one used stratified random sampling (1/17 articles, 5.9%) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles included women from African countries only, including Somalia, Kenya, Sudan, South Sudan, Sierra Leone, Burundi, and Ethiopia (7/19 articles, 36.8%) [ 40 , 46 , 49 , 51 , 52 , 55 , 58 ]. Two articles included women from Syria (2/19 articles, 10.5%) [ 43 , 50 ], two included women from Nepal (2/19 articles, 10.5%) [ 48 , 53 ], one focused on women from Mexico (1/19 articles, 5.3%) [ 47 ], and one included women from mainland China (1/19 articles, 5.3%) [ 54 ]. Four articles included women from countries across continents, including Uganda, Iraq, Bosnia, India, Myanmar, Afghanistan, Sri Lanka, and Russia (4/19 articles, 21.1%) [ 41 , 44 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But undocumented immigrants’ fetuses are not always, only, or simply excluded; they are selectively included, excluded, or positioned hierarchically in relation to the gestating person. As Skye de Saint Felix (2019) shows, the ORR’s denial of Doe’s abortion request is underwritten by racialized, gendered pathologization of pregnant immigrants. Even so, the ORR’s ban on “facilitating” abortions and their director’s openly pro-life rhetoric (Winterberger 2019) contradict the conclusion that undocumented immigrants’ fetuses cannot be represented as fetal citizens who deserve state protection.…”
Section: Literature Review: Two Logics Of Citizenshipmentioning
confidence: 99%